Uvajalna sredstva pregovorov z južnoslovansko nacionalno oznako v korpusu starejše in sodobne slovenščine - Ulčnik, Natalija (Slavia Centralis, 2020)
TEXT INTRODUCERS OF THE PROVERBS WITH A SOUTH SLAVIC NATIONAL DESIGNATION IN THE OLD AND CONTEMPORARY SLOVENE CORPUSThe article highlights the text introducers of the proverbs with the South Slavic national linguistic designation e.g. Slovene proverb, as the Croatian proverb says, as the Serbian proverb says, according to the famous Bosnian proverb. The material was taken from both old and contemporary texts corpuses (IMP, Gigafida) and was analysed and compared at the level of form, position, meta-linguistic marks and communication value. The analysis also includes various options of incorporating foreign linguistic units. In addition to the general functions of text introducers, special functions related to the use of the national designation are also highlighted.
Keywords: paremiology; Slovene language; South Slavic language area; language corpus; corpus IMP; corpus Gigafida